Oral Health-Related Quality of Life in People with Achalasia - Hanisch, Marcel (Medicina (Kaunas), 2020)
Background and Objective: The oral health-related quality of life (OHRQoL) of patients with achalasia has not been evaluated to date. Therefore, the aim of this study was to assess the OHRQoL of patients with achalasia and to get information about the time taken for diagnosis and oral symptoms. Materials and Methods: The study was conceived of as an anonymous epidemiological survey study in people with achalasia in order to assess their OHRQoL in each case. For this, a questionnaire was developed consisting of free-text questions and of the standardized German version of the OHIP-14 questionnaire. Results: In total, forty-four questionnaires were analyzed including 31 female and 13 male participants. Regardless of gender, the mean age was 50.57 years (range: 17–78). Of the surveyed individuals, seventy-nine-point-five-five percent had been diagnosed between 25 and 60 years of age. The period from the first signs of the disease to diagnosis was 6.15 years, irrespective of gender. The overall OHIP-14 score without gender differentiation was 8.72 points (range 0–48); the mean score of female participants was 11.13 (range: 0–48), and the OHIP score of male participants was 3.15 on average. Two participants reported oral symptoms. Conclusions: The already known problem of the delayed diagnosis of rare diseases was also confirmed in the case of achalasia. Females with achalasia seemed to be significantly affected by lower OHRQoL than males with achalasia and women of the general population. Demineralization of the tooth structure was described in two participants.